Peningkatan Kemampuan Membaca Al-Qur’an Siswa Melalui Metode Qitada - Habibah, Popi Nurlaila; Nurteti, Lilis (Tsamratul Fikri | Jurnal Studi Islam, 2019)
This classroom action research article produced several findings, namely: (1) The teacher experienced an increase in the ability to develop learning plans using the Qitada method, cycle I 79.92, cycle II 84.28 and cycle III 88.07; (2) The teacher has increased the ability to carry out learning using the Qitada method, first cycle 80.93, second cycle 86.33 and third cycle 91.7; (3) the students' ability to read the Koran using the Qitada method has increased, namely pre cycle 75.6, cycle I 77, cycle II 79.30 and cycle III 80.56.